Hyperwheel decompositions of λ-fold complete bipartite 3-uniform hypergraphs λKn,n(3) - Zhao, Hongtao; Dong, Nannan (Utilitas Mathematica, 2020)
In this paper, we consider a generalization of graph decomposition, called hypergraph decomposition. We show that a decomposition of a λ-fold complete bipartite 3-uniform hypergraph λKn,n(3) into hyperwheel exists if and only if λn(n - 1) = 0 (mod 4) and n ≥ 3. © 2020 Utilitas Mathematica Publishing Inc.. All rights reserved.